Green Synthesis of Antileishmanial and Antifungal Silver Nanoparticles Using Corn Cob Xylan as a Reducing and Stabilizing Agent - Rony Lucas Silva Viana; Gabriel Pereira Fidelis; Mayara Jane Campos Medeiros; Marcelo Antonio Morgano; Monique Gabriela Chagas Faustino Alves; Luiz Felipe Domingues Passero; Daniel Lima Pontes; Raquel Cordeiro Theodoro; Thales Domingos Arantes; Diego Araujo Sabry; Guilherme Lanzi Sassaki; Raniere Fagundes Melo-Silveira; et al. (Biomolecules, 2020)
Corn cob is an agricultural byproduct that produces an estimated waste burden in the thousands of tons annually, but it is also a good source of xylan, an important bioactive polysaccharide. Silver nanoparticles containing xylan (nanoxylan) were produced using an environmentally friendly synthesis method. To do this, we extracted xylan from corn cobs using an ultrasound technique, which was confirmed by both chemical and NMR analyses. This xylan contained xylose, glucose, arabinose, galactose, mannose, and glucuronic acid in a molar ratio of 50:21:14:9:2.5:2.5, respectively. Nanoxylan synthesis was analyzed using UV–vis spectroscopy at kmax = 469 nm and Fourier transform infrared spectroscopy (FT-IR), which confirmed the presence of both silver and xylan in the nanoxylan product. Dynamic light scattering (DLS) and atomic force microscopy (AFM) revealed that the nanoxylan particles were ~102.0 nm in size and spherical in shape, respectively. DLS also demonstrated that nanoxylan was stable for 12 months and coupled plasma optical emission spectrometry (ICP-OES) showed that the nanoxylan particles were 19% silver. Nanoxylan reduced Leishmania amazonensis promastigote viability with a half maximal inhibitory concentration (IC50) value of 25 μg/mL, while xylan alone showed no effective. Additionally, nanoxylan exhibited antifungal activity against Candida albicans (MIC = 7.5 μg/mL), C. parapsilosis (MIC = 7.5 μg/mL), and Cryptococcus neoformans (MIC = 7.5 μg/mL). Taken together, these data suggest that it is possible to synthesize silver nanoparticles using xylan and that these nanoxylan exert improved antileishmanial and antifungal activities when compared to the untreated polysaccharide or silver nitrate used for their synthesis. Thus, nanoxylan may represent a promising new class of antiparasitic agents for use in the treatment of these microorganisms.